2015
DOI: 10.3390/mi6101435
|View full text |Cite
|
Sign up to set email alerts
|

Droplet Microfluidic Technique for the Study of Fermentation

Abstract: Abstract:We demonstrate a technique that uses microdroplets for culturing and selecting bacterial cultures in a model biotechnological application. We propose an assay for determination of ethanol concentration that provides increased dynamic range and is compatible with droplet microfluidic screening technologies. The assay comprises two enzymes-alcohol oxidase (AOX) and horseradish peroxidase (HRP)-and a colorimetric readout system of phenol-4-sulfonic acid (PSA) and 4-aminoantipyrine (4-AAP). The microdropl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…103 Droplet microfluidic assays have also been developed for estimating the alcohol production rate of microbes using enzymatic assays. 104,105 Multiple fluorescent markers can be detected/monitored simultaneously in droplet cultures. Shim et al presented a microfluidic device that was capable of trapping and storing picoliter droplets.…”
Section: Applications Of Droplet Microfluidics In Microbiologymentioning
confidence: 99%
See 1 more Smart Citation
“…103 Droplet microfluidic assays have also been developed for estimating the alcohol production rate of microbes using enzymatic assays. 104,105 Multiple fluorescent markers can be detected/monitored simultaneously in droplet cultures. Shim et al presented a microfluidic device that was capable of trapping and storing picoliter droplets.…”
Section: Applications Of Droplet Microfluidics In Microbiologymentioning
confidence: 99%
“…[179][180][181] However, the high elasticity of PDMS makes it difficult to precisely control the flow of long sequences of droplets due to slow flow caused by relaxation of pressure. Recent approaches proposed the use of chips and tubing made of stiff materials such as polycarbonate, 7,105,113 polyIJtetrafluoroethylene) (PTFE, Teflon) 100,112 or fluorinated ethylene propylene (FEP). 5,6 New methods of fabrication and modification of stiff polymers should be developed for systems for long-term culturing of bacteria without wetting or excessive emulsification.…”
Section: Wetting and Cross-contaminationmentioning
confidence: 99%
“…The proposed method was successfully applied to the analysis of 12 distinct categories of alcoholic drinks with ethanol concentrations ranging from 5% v/v for beer to 53 percent v/v for scotch whiskey. Churski et al [92] demonstrated a microfluidic platform for determining the concentration of ethanol in micro-droplets (Fig. 2C).…”
Section: Ethanol Concentrationmentioning
confidence: 99%
“…The sensitivity of this device is higher than that of breathalyzers, and the device can work in a wide ROD of 0.0005-0.6 g/L. Droplet microdroplet screening is utilized to determine ethanol levels in cell cultures (Scheme 20 B) [461]. The prototype is based on an electrochemical alcohol oxidase/HRP sensor, and it provides a useful device for detecting the alcohol consumption of drivers.…”
Section: Scheme 19mentioning
confidence: 99%